Intercultural Communicative Competence Model Using English Literature: A Case Study at Some Islamic Universities in Indonesia - Juliastuti; Magfirah Thayyib; Haerazi Haerazi (Register Journal, 2023)
The acquisition of intercultural competence is considered paramount in enabling learners to engage comfortably with individuals from diverse linguistic and cultural backgrounds. The ability to communicate and interact appropriately with individuals from diverse cultural and linguistic backgrounds is increasingly recognized as a fundamental component of the 21st century learning skillset. To investigate the attitudes, knowledge, and skills of students in relation to intercultural activities, this study employs a literature-based instructional approach. The implementation of the Intercultural communicative competence through English Literature (ICC-EL) paradigm among 92 students enrolled in the English Education Study Program at an Islamic higher education institution is the subject of this study. The research adopted a mixed-method approach to generate both quantitative and qualitative data. Specifically, a questionnaire was administered to students upon the completion of the course to elicit quantitative data, while qualitative data was obtained through observation of the students' performance by the course lecturer. The results demonstrate that the implementation of the ICC-EL model has proven to be successful in stimulating the students' intercultural communication skills. Furthermore, the study of literary materials in the form of English novels has encouraged students to administer their awareness of intercultural communication skills. The incorporation of a variety of techniques has provided students with greater exposure to diverse languages and cultures, thereby encouraging them to manage their intercultural communication skills. The assessment of intercultural communication competency employed in the ICC-EL model is deemed appropriate and adaptable for implementation in different language teaching and evaluation contexts.